Developing insights into contemporary con(pro)sumer culture based on classical ideas in social theory. (20th February 2017) - Ritzer, George
Abstract : Purpose: The purpose of this paper is to address the concern for prosumption, created by Alvin Toffler's work, and its fusion with Marx's ideas to create the view that the people now live in an era of prosumer (rather than producer or consumer) capitalism. As a social theorist, the author routinely studies the ideas of classical (and contemporary) theorists not only to understand their thinking, but also for ideas that he can use, and expand upon, to better understand contemporary society, especially the economy. The author has used the ideas of Max Weber on rationalization – to develop his thinking on McDonaldization, and his ideas on enchantment and disenchantment – in the development of the author's thinking on the cathedrals of consumption. The latter can also be seen as means of production from the perspective of Karl Marx's theories. Georg Simmel's theorizing about money led the author to insights on credit cards, especially the greater temptation to imprudence associated with them in comparison to cash. More recent postmodern theory helped the author understand the mechanisms (e.g. simulations) by which the cathedrals of consumption have undergone a process of enchantment. Design/methodology/approach: This is a work in historical theory and metatheory. Findings: The careful review of classical (and contemporary) social theories could, when adapted, help us to better understand contemporary society, especially, in this case the economy. Research limitations/implications: This is not a piece of research, but rather a theoretical exploration of contemporary prosumer culture based on classical ideas in social theory. It implies a radical change in the thinking about the modern economy. Originality/value: This essay brings together some of the author's ideas – and their classical roots – to offer an original perspective on the contemporary economy.